2016
DOI: 10.3139/217.3242
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity-Based Product Design: Utilizing the Polymorphism of Isotactic PP Homo- and Copolymers

Abstract: The polymorphism of isotactic polypropylene (iPP) in combination with the strong response of this polymer to nucleation can be utilized for expanding the application range of this versatile polymer. Based on three “case studies” related to β-iPP pressure pipes, ethylene-propylene (EP) random copolymers for thin-wall injection molding and transparency and sterilization resistance of cast films we demonstrate ways of combining polymer composition, nucleation and process settings to achieve the desired applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…In this concentration range the peak temperature of PP/DMDBS decreases. The step in the peak temperature could be caused by the formation of a nanostructured network of the nucleating agents which changes the character of the main crystallization process and could be related to the formation of shish‐kebab‐like structure as is found for PP/DMDBS and PP/TBPMN . Process 4 occurs only at high content of TBPMN and at high temperatures; its dependence on content shows no clear trend.…”
Section: Resultsmentioning
confidence: 96%
“…In this concentration range the peak temperature of PP/DMDBS decreases. The step in the peak temperature could be caused by the formation of a nanostructured network of the nucleating agents which changes the character of the main crystallization process and could be related to the formation of shish‐kebab‐like structure as is found for PP/DMDBS and PP/TBPMN . Process 4 occurs only at high content of TBPMN and at high temperatures; its dependence on content shows no clear trend.…”
Section: Resultsmentioning
confidence: 96%
“…Thermal stability and the amount of filler in the different compositions used in this study were Polypropylene has a very rich polymorphism and it has been reported that filler inclusion has an effect of the overall morphology of filled systems [39]. The iPP used in this work shows generally a large tendency to form crystals in β phase, mostly due to the high purity of this system [66]. The presence of β phase for the pure material is clearly observed from the [300]β peak in Figure 9.…”
Section: Thermal Propertiesmentioning
confidence: 88%
“…Furthermore, due to the 3D hierarchical filler morphology and subsequent filler distortions during the preparation stage, the ability to access the primary graphene particle from mechanical point of view needs to be tested. The filler has also been shown to have strong nucleation effects [27,56], resulting in an alteration of the crystalline structure, that can have a significant impact on the mechanics of the system. In this context, we focus on dynamic, tensile, impact, and creep properties of the novel 3D hierarchical reduced graphene oxide.…”
Section: Introductionmentioning
confidence: 99%